REPRESENTASI GIBRAN RAKABUMING RAKA DALAM TEKS OPINI TEMPO.CO NOVEMBER 2023: ANALISIS WACANA KRITIS - Dalil Maulana, Abang Muhammad; Merry Andriani (SEBASA Jurnal Pendidikan Bahasa dan Sastra, 2024)
The primary data consists of political opinion texts discussing Gibran Rakabuming Raka, while the secondary data includes written works, newspapers, research, and related journals. Data collection methods involve the Observation technique with Eavesdropping Technique, Uninvolved Conversation Observation Technique, and Note-taking Technique. The findings provide a deeper understanding of opinion texts portraying Gibran Rakabuming Raka as an unfit candidate for vice president due to legal process issues and the apparent bias of Tempo magazine in its reporting. This study also contributes to the enrichment of critical discourse analysis on political and media issues.